Migration And Agricultural Transformation in the Nandom District - Tetteh, F. O. (University of Ghana, 2025)
The implications of out-migration on agricultural transformation have been a topical issue over the years. The mixed effects of the transformation brought about because of people migrating out of communities of origin have been the bone of contention among scholars in migration research. This study, therefore, sought to find out the relationship between agricultural transformation and migration using the Nandom Municipal District as a study area. The study was guided by three main objectives, which shaped the entire discussion and the exact communities sampled. The study adopted the mixed method using a sample size of 150 respondents for the survey using probability and non-probability sampling techniques at different stages of the study. SPSS version 21.0 was used to analyze the primary survey data after going through all the required ethical procedures. The study found that the communities in the Nandom Municipality are predominantly agricultural based, and migration to urban areas is a common phenomenon among the residents. Seasonal migration is common amongst residents, especially during the dry season. Nonetheless, the majority of the movements are within Ghana. Chieftaincy disputes, lack of a ready market for agricultural produce among others are not the reasons for which people migrate from the community rather; famine, long droughts due to changing climate, poor soils, poor health and educational services infrastructure and delivery, bad road networks, poor crop yields, improper housing facilities are considered by participants as the main reasons why many people migrate out of the communities in the area. Regarding the implications of the out-migration of migrants on the agriculture sector in the study area, the study found that migrant networks have helped left behind relatives to diversify their source of livelihood by establishing agro-chemical and other businesses which provide different services. Both cash and social remittances have helped transform the agriculture sector even though it is insignificant in comparative terms. The perspective of the implications of outmigration on community transformation, according to most study participants, is positive despite the challenges identified. Several recommendations are also offered at the end of this work.
MPhil. Migration Studies
Keywords: out-migration; agricultural transformation; Nandom Municipal District